ANALYSIS OF LIQUIDITY, SOLVENCY, AND PROFITABILITY RATIOS TO ASSESS THE COMPANY FINANCIAL PERFORMANCE OF PT. INDOFOOD CBP SUKSES MAKMUR, TBK - Hendri Sembiring (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2020)
The purpose of this study was to assess the company financial performance of PT. Indofood CBP Sukses Makmur, Tbk using financial ratio analysis for the period 2016-2018. The financial ratios used are liquidity, solvency, and profitability. This type of research is a case study. Data collection techniques used are documentation and literature. The results of this study indicate that the liquidity ratio in 2016-2018 can be seen from the current ratio, which is good. The quick ratio in 2016 and 2017 results are good, while in 2018 it is not good. The cash ratio in 2016-2018 are good. The solvency ratio measured using DAR in 2016 and 2017 are not good while in 2018 is good. The DER in 2016-2018 is good. ROA profitability ratio in 2016-2018 results are not good, ROE in 2016-2018 results are not good, GPM in 2016-2018 results are good, and NPM in 2016-2018 results are not good, OPM in 2016-2018 results are not good, and ROA in 2016- 2018 results are not good. Keywords: Liquidity , Solvency, Profitability Ratios.